Manajemen Sarana Prasarana dalam Menunjang Proses Pembelajaran : Infrastructure Management in Supporting the Learning Process - Srifariyati, Srifariyati; Susianti, Oni Marliana; Lukman, Lukman (STAI Publisistik Thawalib Jakarta, 2024)
Management of facilities and infrastructure in schools is a crucial activity that greatly influences the success of the learning process. This research aims to understand the management of facilities and infrastructure in the learning process of group B1 at kindergarten 17 Teladan Sugar Factory Sumberharjo, Pemalang District. The research adopts a qualitative approach with a case study design. Primary data is obtained from the school principal, educators, and parents, while secondary data is gathered from relevant documents and records. Data collection techniques include observation, interviews, and documentation. Data processing involves reduction, data presentation, and drawing conclusions. Research findings indicate that planning: is conducted through discussions with teachers and parents, along with short, medium, and long-term school programs. Procurement: realized through funding from operational assistance and parental contributions. Arrangement: carried out by placing learning facilities according to the needs in classrooms and schoolyards. Utilization: is the responsibility of all school members, with routine maintenance every Friday. Disposal: This is done by storing damaged items or disposing of unused ones. Inhibiting factors include limited funds, lack of specialized management, and parental cooperation in fundraising. Supporting factors include committee involvement, financial support, and student numbers. Conclusion: facility management has been maximized, leading to quality learning outcomes.